Vaccine Adduct Microneedle Fabrication through 3D Printing Technology: A State-of-Art Review - Kumari, Mamta (Asian Journal of Pharmaceutics (AJP), 2023)
The use of attractive, minimally invasive puncture devices called microneedles (MNs) penetrates the skin without discomfort and enables the transdermal administration of active substances, including drugs and vaccines. MNs are also significant in disease diagnosis, monitoring, and cosmetics. MN geometry and shape are essential factors in affecting performance and therapeutic efficacy, whereas traditional manufacturing techniques including molding might not be able to enable fast design changes. In this regard, the manufacturing of MNs through the use of 3D printing technology allows for the quick and precise development of complicated MN prototypes as well as the availability of MN devices that may be configured to have the appropriate shape and dimension. Additionally, by combining MNs with 3D printing exhibits significant promise for the production of efficient transdermal drugs and vaccine delivery systems as well as medical devices. Unlike traditional intramuscular or subcutaneous delivery using hypodermic needles, MN-based vaccine created by 3D printing technology distributes vaccine directly into the skin, which is thought to be an immunologically far more relevant vaccination location than underlying tissue. The purpose of this review is to convey the benefits of using 3D printing technology as a novel tool for MN fabrication. Different 3D printing techniques are shown, and typical MNs produced using such techniques are highlighted in detail.